PENGARUH CAR, LDR, NPL, DAN BOPO TERHADAP KINERJA PERBAKAN DI BURSA EFEK INDONESIA TAHUN 2013 – 2106 - Lela Marina, 15.05.61.0013; Sudarsi, sri (Students' Journal of Economic and Management, 2019)
This study aims to test and analyse the effect of Capital Adequacy Ratio, Loan to Deposit Ratio, Non-Performing Loan, and BOPO towards profitability (Return on Assets) of Banking Companies listed on Indonesia Stock Exchange period of 2013 – 2016. This study used purposive sampling method with sample size as 108 banking companies. Hypothesis testing using t-test with 5% significance level. The result showed that Capital Adequacy Ratio has negative significant effect toward Return on Assets, Loan to Deposit Ratio and Non- Performing Loan has no effect toward Return on Assets, while BOPO has negative and significant effect toward Return on Assets.